STRATEGI PENGEMBANGAN PARIWISATA BERKELANJUTAN PADA OBJEK WISATA ALAM DI BANDAR LAMPUNG: STRATEGI PENGEMBANGAN PARIWISATA BERKELANJUTAN PADA OBJEK WISATA ALAM DI BANDAR LAMPUNG - Melsadila, Mely; A . Efendi, A . Efendi; Nugeraha, Prasetya (Jurnal Kompetitif Bisnis, 2023)
Natural attraction is a form of recreation and tourism that utilizes available natural resourches. The uniqueness of tourism is the main attraction for tourists. This study aims to determine how much influence tourist attraction and destination image on revisit intention for natural tourism objects in Bandar Lampung. The population in this study are 854.084 natural tourism objects visitors in Bandar Lampung and the sample amounted to 100 respondents who were taken using the technique purposive sampling. The kinds of data used were primary and secondary data. Data were collected by using a questionnaire. The data in this study were analyzed using multiple linear regression analysis. The results of this study indicate variable tourist attraction partially significant effect on revisit intention, variable destination image partially significant effect on revisit intention. While the results are simultaneously variable tourist attraction and destination image significant effect on revisit intention with value R Square of 0.594 or 5.94%.